Dari Penafsiran Yang Keras Ke Lembut: Kontekstualisasi QS. at-Taubah [9]: 5 Melalui Lensa Double Movement Fazlur Rahman - Syarifah Zifa Putri Andini (Contemporary Quran, 2025)
QS. At-Taubah [9]: 5 has often been interpreted literally by classical exegetes and some modern commentators as a command to kill polytheists, thereby giving the verse a tone of violence. Such interpretations tend to overlook the historical context and moral objectives of the verse, thus limiting the possibility of uncovering more contextual and ethical meanings. This study therefore seeks to reveal a more tolerant understanding of QS. at-Taubah [9]: 5 through Fazlur Rahman’s double movement hermeneutical approach. The main focus is to analyze the verse’s original meaning, the historical and sociological context at the time of its revelation, and how this approach can contextualize the verse so as to draw out the ethical values that have often been neglected in traditional exegesis. To achieve this aim, the research employs a qualitative approach using a literature review method to examine QS. at-Taubah [9]: 5 through a hermeneutical lens, in order to uncover its potential for a more contextual meaning. The findings indicate that, textually, QS. at-Taubah [9]: 5 contains imperative forms such as “kill” and “capture.” However, from both linguistic and exegetical perspectives, these commands are contextual and directed solely toward polytheists who had violated a peace treaty. The verse was revealed after the conquest of Mecca, when the Muslim community had become the dominant power, and the command to fight was issued in response to threats posed by polytheist groups who had breached their commitments to peace. Through the hermeneutical framework, the meaning of this verse is contextualized so that it aligns with the ethical principles of Islam, which reject violence except in defense against a genuine threat. This study demonstrates that the verse commonly classified as an ayat qital (verse of fighting) does not, in fact, promote violence. Rather, it underscores values of justice, peace, and tolerance, principles that are fully consistent with the ideal of peaceful coexistence in modern societies such as Indonesia.